Xanthones from Swertia mussotii as Multitarget‐Directed Antidiabetic Agents. Issue 7 (31st January 2014) - Zheng, Huan‐Huan; Luo, Cui‐Ting; Chen, Heru; Lin, Juan‐Na; Ye, Chun‐Ling; Mao, Shuang‐Shuang; Li, Yu‐Lin
Abstract Oxidative stress has been suggested to play a causative role in the development of obesity‐induced insulin resistance and type 2 diabetes. Given the antioxidant potency of previously reported xanthones isolated from Swertia mussotii. These natural products were further evaluated against other targets in diabetes, aldose reductase and α‐glucosidase, in order to identify novel multitarget‐directed antidiabetic agents. Among the 14 xanthones screened, 1, 3, 7, 8‐tetrahydroxyxanthone (6), 1, 3, 5, 8‐tetrahydroxyxanthone (7), and 2, 3, 6, 8‐tetrahydroxyxanthone‐7C‐(β‐D‐glucoside) (12) were confirmed as good antioxidants and α‐glucosidase inhibitors. Xanthone 7 was also confirmed as a potent inhibitor of aldose reductase (ALR2). Xanthone 7 was the most active α‐glucosidase and ALR2 inhibitor, with IC50 values of 5.2±0.3 μM and 88.6±1.6 nM, respectively, while compound 12 was shown to be the most active antioxidant. Given the overall profile, xanthone 7 is considered to be the most promising multitarget antidiabetic agent, and may have potential for the treatment of both diabetes and diabetic complications.